Revitalizing Ukrainian cities - Kruhlov, Vitalii (Central European Public Administration Review, 2024)
Purpose: The article examines the role of public-private partnership (PPP) as a key tool for urban infrastructure restoration and the development of Ukrainian cities within the framework of the Smart City concept. It underscores the urgent need for effective mechanisms to restore urban infrastructure, especially in light of the challenges associated with the Russian military aggression and the resulting destruction in Ukrainian cities. The study explores key aspects of smart cities development, including the integration of digital technologies, the use of data, and innovative business models aimed at optimizing city functions. Design/Methodology/Approach: The research employs a multi-stage methodological approach, encompassing elements such as gauging urban population satisfaction with municipal services, graphical analysis using CIMI, assessing the relevance of revitalizing Ukrainian cities and the need for mobilizing business resources, sociological surveys, developing a Smart City model based on PPP project outcomes, and formulating key elements of the national Smart City development strategy. Findings: Emphasizing the importance of strategic planning and cooperation between public and private sectors, the study demonstrates the advantages offered by PPP-based projects. The obtained results highlight the pivotal role of PPPs in promoting urban development initiatives basedon the Smart City concept. The study emphasises the potential of PPPs in shaping stable and prosperous smart cities in Ukraine. Through effective PPP utilisation, local governments can restore urban infrastructure,improve service quality, and enhance the quality of life for their citizens. Practical Implications: The research results can serve as the basis for strategic planning and investment in infrastructure projects necessary for the creation of a smart city. The envisioned strategy will allow for the improvement of legislative acts covering a wide range of aspects of smart cities development while promoting collaboration between public and private entities. This includes bolstering the transportation system, deploying digital technologies, modernizing social institutions, and enhancing the efficiency of urban resource management. Originality/Value: The originality and value of the study lie in its multifaceted approach to assessing and promoting the Smart City concept in Ukrainian urban development. It combines various research methods, including satisfaction assessments, CIMI-based graphical analyses, sociological surveys, and the development of a Smart City model based on PPP project results. This approach not only provides a comprehensive understanding of the state of urban infrastructure and citizen satisfaction but also offers a strategic framework for smart cities development.Purpose: The article examines the role of public-private partnership (PPP) as a key tool for urban infrastructure restoration and the development of Ukrainian cities within the framework of the Smart City concept. It underscores the urgent need for effective mechanisms to restore urban infrastructure, especially in light of the challenges associated with the Russian military aggression and the resulting destruction in Ukrainian cities. The study explores key aspects of smart cities development, including the integration of digital technologies, the use of data, and innovative business models aimed at optimizing city functions. Design/Methodology/Approach: The research employs a multi-stage methodological approach, encompassing elements such as gauging urban population satisfaction with municipal services, graphical analysis using CIMI, assessing the relevance of revitalizing Ukrainian cities and the need for mobilizing business resources, sociological surveys, developing a Smart City model based on PPP project outcomes, and formulating key elements of the national Smart City development strategy. Findings: Emphasizing the importance of strategic planning and cooperation between public and private sectors, the study demonstrates the advantages offered by PPP-based projects. The obtained results highlight the pivotal role of PPPs in promoting urban development initiatives basedon the Smart City concept. The study emphasises the potential of PPPs in shaping stable and prosperous smart cities in Ukraine. Through effective PPP utilisation, local governments can restore urban infrastructure,improve service quality, and enhance the quality of life for their citizens. Practical Implications: The research results can serve as the basis for strategic planning and investment in infrastructure projects necessary for the creation of a smart city. The envisioned strategy will allow for the improvement of legislative acts covering a wide range of aspects of smart cities development while promoting collaboration between public and private entities. This includes bolstering the transportation system, deploying digital technologies, modernizing social institutions, and enhancing the efficiency of urban resource management. Originality/Value: The originality and value of the study lie in its multifaceted approach to assessing and promoting the Smart City concept in Ukrainian urban development. It combines various research methods, including satisfaction assessments, CIMI-based graphical analyses, sociological surveys, and the development of a Smart City model based on PPP project results. This approach not only provides a comprehensive understanding of the state of urban infrastructure and citizen satisfaction but also offers a strategic framework for smart cities development.
Keywords: infrastructure; infrastruktura; javna uprava; javno-zasebno partnerstvo; obnova; okrevanje; orodja; pametno mesto; public administration; public-private partnership; rebuilding; recovery; smart city; tools; Ukraine; Ukrajina